Optimization of Bay Leaf and Garlic Extract Concentrations as Natural Preservatives in Tofu: Exploring a Novel Approach in Food Preservation - Parisma, Wan Intan; Safitri, Khoerunnisa; Saputra, Roni; Gemala, Mega (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: The use of synthetic preservatives such as formalin in food products, especially tofu, has raised serious health concerns, including the risk of cancer. Objective: As a solution, this study aims to evaluate the potential combination of bay leaf extract (Syzygium polyanthum) and garlic (Allium sativum) as a natural preservative to replace synthetic preservatives in tofu. Method: The study was conducted using a completely randomized block design (RCBD) with variations in extract concentration and tofu storage duration, as well as testing of physicochemical, microbiological, and sensory characteristics. Results and Discussion: The results showed that bay leaf extract produced a dark green color with a strong aroma, while garlic extract maintained a white color with a distinctive aroma without changes in texture. The combination of both extracts gave a complex aroma but showed black spots and mold growth on the 6th day of storage. Microbiologically, the combination of bay leaf and garlic extracts effectively reduced the number of Escherichia coli to below the detection limit, but slightly increased the total coliform count. Conclusion: The conclusion of the results is there the combination of bay leaf and garlic extracts can improve the sensory quality of tofu and reduce pathogenic bacteria, but further management is needed to ensure the microbiological safety of the product.